Expression of PD-1, PD-L1, and PD-L2 in posttransplant lymphoproliferative disorder after solid organ transplantation. Issue 2 (28th January 2019) - Kinch, Amelie; Sundström, Christer; Baecklund, Eva; Backlin, Carin; Molin, Daniel; Enblad, Gunilla
Abstract: We studied the expression of programed death 1 (PD-1) receptor and its ligands (PD-L1/-L2) by immunohistochemistry and its association with clinicopathological features in 81 posttransplant lymphoproliferative disorders (PTLDs) following solid organ transplantation. Overall, 67% (54/81) of the PTLDs were positive in any of the three immunostainings. PD-1 was detected on tumor-infiltrating cells in 41% (33/81) of the PTLDs. PD-L1 was expressed on ≥5% of the tumor cells in 50% (40/80) and PD-L2 in 32% (23/72) of the PTLDs. All Burkitt lymphomas were PD-L1 negative. Expression of PD-L1 tended to be associated with non-germinal center-type of diffuse large B-cell lymphoma (63% vs. 33% in GC-type, p = .14) and latent membrane protein-1+ PTLD (76% vs. 44% in LPM1-, p = .09). Heart recipients had more frequent PTLDs with PD-1+ microenvironment ( p = .01). The frequent expression of PD-1 or -L1/-L2 in PTLD warrants further clinical evaluation of the efficacy and safety of PD-(L)1 inhibitors for refractory PTLD.